The Extraterritoriality Nexus: Manifestation of Extraterritoriality as Natural Phenomenon in Urban Context - Fessel, Melanie (Consilience, 2013)
Architecture and urban planning have to be renegotiated in the context of an increasingly globalized world, where immeasurable human impressions are so complexly woven that it is becoming increasingly difficult to maintain a distinction between nature, culture and the built environment. Within these global networks are our ever-changing cities and landscapes. Fragmented exceptions, defined as geographically autonomous zones of extraterritoriality, disseminate these cities, bringing unstable processes and mutated landscapes that will undeniably affect our futures.